Análise da influência do agente umectante na estabilidade reológica e avaliação de cristais líquidos em formulações cosméticas - Silva, Silas Arandas Monteiro e; Rigon, Roberta Balansin [UNESP]; Valarini, Michele Fernanda Costa; Chorilli, Marlus [UNESP]; Leonardi, Gislaine Ricci (My University, 2013)
Eight cosmetics preparations were developed using different humectants agents in different concentrations. The systems were submitted to physicochemical stability analysis, represented by organoleptic characterization tests, pH determination and centrifugation, once described in T0, T24h, T30 and T60 days. For stable cosmetics basis followed with the analysis to configure the rheological behavior of each preparation. The rheological parameters considered as an object of interest were: flow rate, hysteresis area and apparent viscosity. Analysis was performed applying microscopy of polarized light to investigate the presence of liquid-crystals.. It was verified the presence of liquid-crystals in all preparations, and these lamellar structures are also designed as "Maltese Cross". The presence of these mesogenic structures makes it possible to characterize positively these preparations. It is evident also that the humectant used in such preparations can influence the rheological stability of the same, especially in the parameter described as apparent viscosity. This latter finding, in turn, should be considered as a characterization that can be made a criterion for selection of constituents who have set a cosmetic in the process of design formulation.

Oito bases cosméticas foram desenvolvidas empregando diferentes agentes umectantes, em diferentes concentrações. Os sistemas obtidos foram submetidos às análises físico-químicas de estabilidade, representadas pelos ensaios de caracterização organoléptica, determinação de pH e teste de centrífuga, em tempos descritos em T0, T24h, T30 dias e T60 dias. Para as bases estáveis, se prosseguiu com a realização de análises reológicas para configurar o comportamento de cada sistema emulsionado. Os parâmetros reológicos considerados objeto de interesse foram: índice de fluxo, área de histerese e viscosidade aparente. Foram executadas análises em microscopia de luz polarizada visando investigar a presença de cristais-líquidos e suas configurações espaciais. Constatou-se a presença de cristais-líquidos em todos os sistemas emulsionados, sendo estas estruturas lamelares também concebidos como “cruzes-de-malta”. A presença destas estruturas mesógenas possibilita caracterizar positivamente as preparações. Evidencia-se também que os umectantes utilizados em tais preparações podem influenciar no comportamento reológico das mesmas, sobretudo no parâmetro descrito como viscosidade aparente. Esta última constatação, por sua vez, deve ser analisada como uma caracterização passível de ser tornar um critério para escolha dos constituintes que configuraram uma formulação cosmética no processo de delineamento de novos produtos.
Analysis of the humectant agent influence on the rheological stability and evaluation of liquid crystal in cosmetic formulations
Keywords: Cosmetics; Pseudoplastic; Cosmetic technology; Rheology; Cosméticos; Pseudoplástico; Tecnologia cosmética; Reologia